Determinants of First‐Ever Stroke Severity in West Africans: Evidence From the SIREN Study - Oladimeji Adebayo; Onoja Akpa; Osahon J. Asowata; Adekunle Fakunle; Fred S. Sarfo; Albert Akpalu; Kolawole Wahab; Reginald Obiako; Morenikeji Komolafe; Lukman Owolabi; Godwin O. Osaigbovo; Akinkunmi Paul Okekunle; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Baseline stroke severity is probably partly responsible for poor stroke outcomes in sub‐Saharan Africa. However, there is a paucity of information on determinants of stroke severity among indigenous Africans. We sought to identify the factors associated with stroke severity among West Africans in the SIREN (Stroke Investigative Research and Educational Networks) study. Methods and Results Stroke was diagnosed clinically and confirmed with brain neuroimaging. Severe stroke was defined as a Stroke Levity Scale score of ≤5. A multivariate logistic regression model was constructed to identify factors associated with stroke severity at 95% CI and a nominal cutoff of 5% type 1 error. A total of 3660 stroke cases were included. Overall, 50.7%% had severe stroke, including 47.6% of all ischemic strokes and 56.1% of intracerebral hemorrhage. Factors independently associated with severe stroke were meat consumption (adjusted odds ratio [aOR], 1.97 [95% CI, 1.43–2.73]), low vegetable consumption (aOR, 2.45 [95% CI, 1.93–3.12]), and lesion volume, with an aOR of 1.67 (95% CI, 1.03–2.72) for lesion volume of 10 to 30 cm3 and aOR of 3.88 (95% CI, 1.93–7.81) for lesion volume >30 cm3. Severe ischemic stroke was independently associated with total anterior circulation infarction (aOR, 3.1 [95% CI, 1.5–6.9]), posterior circulation infarction (aOR, 2.2 [95% CI, 1.1–4.2]), and partial anterior circulation infarction (aOR, 2.0 [95% CI, 1.2–3.3]) compared with lacunar stroke. Increasing age (aOR, 2.6 [95% CI, 1.3–5.2]) and lesion volume >30 cm3 (aOR, 6.2 [95% CI, 2.0–19.3]) were independently associated with severe intracerebral hemorrhage. Conclusions Severe stroke is common among indigenous West Africans, where modifiable dietary factors are independently associated with it. These factors could be targeted to reduce the burden of severe stroke.